Design of a technical english manual for the students of the first level of automotive mechanics at the "Instituto Tecnológico Superior Central Técnico" - Vaca Martínez, Mireya Elizabeth (2007)
To deal with the English language as a matter of study for school or technological students is it necessary for people who design the programs or plans of study to understand the characteristics of a language. The person begins listening and understanding what people say around, then he or she begins to produce oral expressions trying to imitate what is already known orally to get an answer from the people. These two skills are generally acquired at non formal education that means, out of school or before this one. To develop all these skills in a parallel way can take years of constant exposition to diverse manifestations of the language and also requires the constant interaction with other language speakers. This process never stops and forms part of the real life of a person and his development. We would say that the intellectual capacity of a person depends on the complexity level of the language that is able to understand and express orally and in written form .To all this we have to add the role of the culture inside the process of language acquisition. All language grows and depends of a cultural context which leads its development as a tool of communication. Culturally, there are manifestations of some social, scientific, technological or other groups that create new communication needs that make imperative the creation, adoption or modification of new words, phrases and terms to show exactly what the other groups need to understand. This means that, cultural manifestations obligate to a constant language change, especially today when the worldwide communication is part of our reality. This argument is enough to realize the language complexity, and also the difficulty of acquiring a foreign language where the person is far from the place where this language is the mother tongue. Then, the focus of the project is on the poor results got in the English language acquisition in our country and the point of view of the way how to conceive the English language teaching for getting satisfactory results.